Analysis of the 2012 Canadian Community Health Survey-Mental Health demonstrates employment insecurity to be associated with mental illness. Issue 50 (17th December 2021) - Kim, Il-Ho; Choi, Cyu-Chul; Urbanoski, Karen; Park, Jungwee; Kim, Ji Man
Abstract : Abstract: A growing number of people depend on flexible employment, characterized by outsider employment and lower levels of job security. This study investigated whether there was a synergistic effect of employment status and job insecurity on mental disorders. This study used data from the 2012 Canadian Community Health Survey-Mental Health (CCHS) of 13, 722 Canada's labor force population aged 20 to 70. Data were collected from January to December, 2012, using computer-assisted personal interviewing. As combining employment status with perceived job insecurity, we formed five job categories: secure full-time, full-time insecure, part-time secure, part-time insecure employment, and unemployment. Results showed that, regardless of employment status (full-time vs part-time), insecure employment was significantly associated with high risk of mental disorders. Furthermore, the odds ratios for insecure employment were similar to those for unemployment. Male workers who are full-time, but with insecure jobs, were more likely to experience mental disorders than female workers. This study's findings imply that while perceived job insecurity may be a critical factor for developing mental health problems among workers, providing effective health care services can mitigate an excessive health risk for the most vulnerable employment, especially for insecure part-time employment and unemployment.